Microbial food safety : an introduction - Backert, Steffen; Oyarzabal, Omar A. (Food science text series, 2012)
This volume reviews a variety of food safety topics, providing the necessary insight to understand the complexities of the field. Discussions include emerging and reemerging foodborne pathogens, food regulations in the USA, and the most important foodborne pathogens based on food commodities